Modeling Energetic Proton Transport from a Stream Interaction Region to Compound Streams - Xinyi Tao; Fang Shen; Xi Luo (The Astrophysical Journal)
Energetic proton events associated with a stream interaction region (SIR) were observed by two Solar-Terrestrial Relations Observatory (STEREO) and WIND spacecraft from 2007 September 19 to September 25. Different from the measurements of STEREO-A and WIND, the observational data of STEREO-B show additional particle intensity increases when the spacecraft is immersed into the compound stream region with poor compression signatures after the passage of the SIR. In order to investigate this particular event, we simulated proton transport with a solar wind pattern obtained from the two-dimensional analytical model driven by plasma and magnetic field data of the spacecraft. We find that the additional energetic proton event is not an autonomous event created by the compound streams and is closely associated with the accelerated particles in the preceding SIR structure. We highlight the variation in particle distribution as a function of radial distance within the SIR. The magnetic field configuration in the compound stream region observed by STEREO-B provides a more direct connection to the source particle region, which presents a view to explain the differences between the energetic proton observations of the three spacecraft.